1999
DOI: 10.1046/j.1360-0443.1999.9422216.x
|View full text |Cite
|
Sign up to set email alerts
|

The quantification of mortality resulting from the regular use of illicit opiates

Abstract: The mortality rate for illicit opiate users is approximately 13 times greater than for the general population. The large number of years of life lost is reflective of the relatively young population (15-39 years of age) in which opiate-related mortality occurs. Relative risk estimates can also be applied to data on the prevalence of illicit opiate use in other countries to produce locally based aetiological fractions and estimates of person-years of life lost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
126
0
5

Year Published

2004
2004
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(135 citation statements)
references
References 3 publications
4
126
0
5
Order By: Relevance
“…[3][4][5][6][7][8] While mortality rates cannot be directly compared across studies without age or sex adjustment, our results appear to be consistent with other literature reports. A prospective study of mortality among drug users after treatment showed an equally high mortality rate (1.2%), which was six times higher than that for a general, agematched population.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[3][4][5][6][7][8] While mortality rates cannot be directly compared across studies without age or sex adjustment, our results appear to be consistent with other literature reports. A prospective study of mortality among drug users after treatment showed an equally high mortality rate (1.2%), which was six times higher than that for a general, agematched population.…”
Section: Discussionsupporting
confidence: 92%
“…3 Alcohol and drug dependence increase the risk of death substantially. [4][5][6][7][8] As in the general population, death in adults with substance dependence is more common in men than in women. [9][10][11] Similarly, older age is also associated with mortality in this population.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Excess risk of mortality among drug users has been attributed to HIV infection, drug overdosing, and violence. [5][6][7] Fluctuations over time in the relative influence of different causes of death have also been noted.…”
Section: Introductionmentioning
confidence: 99%
“…As compared with those addicted to other drugs, heroin abusers still rely heavily on an i.v. route of administration that places them at greater risk for morbidity as well as premature death due to overdose (1). The neurobiological actions of opiates have been widely studied, and it appears that the rewarding effects of heroin and its psychoactive metabolites, e.g., morphine, are strongly mediated via the opioid receptor (MOR).…”
mentioning
confidence: 99%